CRISPR/Cas9-mediated gene knockout in human adipose stem/progenitor cells. (1st January 2020) - Mandl, Markus; Ritthammer, Heike; Ejaz, Asim; Wagner, Sonja A.; Hatzmann, Florian M.; Baumgarten, Saphira; Viertler, Hans P.; Zwierzina, Marit E.; Mattesich, Monika; Schiller, Valerie; Rauchenwald, Tina; Ploner, Christian; et al.
ABSTRACT: The CRISPR/Cas9 system is a powerful tool to generate a specific loss-of-function phenotype by gene knockout (KO). However, this approach is challenging in primary human cells. In this technical report, we present a reliable protocol to achieve a functional KO in the genome of human adipose stem/progenitor cells (ASCs). Using Sprouty1 ( SPRY1 ) as a model target gene for a CRISPR/Cas9 mediated KO, we particularize the procedure including the selection of the CRISPR/Cas9 target sequences and the employment of appropriate lentiviral vectors to obtain a functional gene KO. The efficiency of CRISPR/Cas9 to mutate the SPRY1 gene is determined by a PCR-based mutation detection assay and sequence analysis. Effects on mRNA and protein levels are studied by RT-qPCR and Western blotting. In addition, we demonstrate that CRISPR/Cas9 mediated SPRY1 KO and gene silencing by shRNA are similarly effective to deplete the Sprouty1 protein and to inhibit adipogenic differentiation. In summary, we show a reliable approach to achieve a gene KO in human ASCs, which could also apply to other primary cell types. Abbreviations: ASC: Adipogenic Stem/Progenitor Cell; Cas: CRISPR-associated system; CRISPR: Clustered Regularly Interspaced Palindromic Repeat; gDNA: Genomic DNA; GOI: Gene of interest; gRNA: Guide RNA; NHEJ: Non-homologous end joining; Indel: In sertion/Del etion; PAM: Protospacer adjacent motif; sWAT: Subcutaneous white adipose tissue; TIDE: Tracking of indels by decomposition